COVID-19 in Southeast Asia Insights for a post-pandemic world - Mckenzie, Murray; Bang Shin, Hyun; OH, DO YOUNG (LSE Press, 2022)
COVID-19 has presented huge challenges to governments, businesses, civil societies, and people from all walks of life, but its impact has been highly variegated, affecting society in multiple negative ways, with uneven geographical and socioeconomic patterns. The crisis revealed existing contradictions and inequalities in society, compelling us to question what it means to return to "normal" and what insights can be gleaned from Southeast Asia for thinking about a post-pandemic world. In this regard, this edited volume collects the informed views of an ensemble of social scientists - area studies, development studies, and legal scholars; anthropologists, architects, economists, geographers, planners, sociologists, and urbanists; representing academic institutions, activist and charitable organisations, policy and research institutes, and areas of professional practice - who recognise the necessity of critical commentary and engaged scholarship. These contributions represent a wide-ranging set of views, collectively producing a compilation of reflections on the following three themes in particular: (1) Urbanisation, digital infrastructures, economies, and the environment; (2) Migrants, (im)mobilities, and borders; and (3) Collective action, communities, and mutual action. Overall, this edited volume first aims to speak from a situated position in relevant debates to challenge knowledge about the pandemic that has assigned selective and inequitable visibility to issues, people, or places, or which through its inferential or interpretive capacity has worked to set social expectations or assign validity to certain interventions with a bearing on the pandemic's course and the future it has foretold. Second, it aims to advance or renew understandings of social challenges, risks, or inequities that were already in place, and which, without further or better action, are to be features of our "post-pandemic world" as well. This volume also contributes to the ongoing efforts to de-centre and decolonise knowledge production. It endeavours to help secure a place within these debates for a region that was among the first outside of East Asia to be forced to contend with COVID-19 in a substantial way and which has evinced a marked and instructive diversity and dynamism in its fortunes.